Scientific Findings on Origin and Attributes of Iron Mentioned in Al-Qur’an - Md. Mamunur Rashid (Journal of Quranic Sciences and Research, 2024)
Sending down the iron for mankind, mentioned in verse 57:25 of Al-Qur’an, is one of the most significant blessings from Allah (SWT). Everything Allah (SWT) provided us, of course, for the needs, uses, and benefits of human beings. The mention of sending iron and its attributes (strong power and benefits for the people) in the Qur’an must have special significance, whether we comprehend it or not. The interpreters of Al-Qur’an explained the origin and the attributes of iron according to their contemporary pieces of knowledge. Modern scientific knowledge provides us the opportunity to uncover a better understanding of the origin of iron as well as its attributes. This research work aims to identify, explore, and demonstrate the findings regarding the origin and the attributes of iron mentioned in Al-Qur’an, through the study of modern scientific resources. All the required information & data, for this research, have been taken from the relevant and available online sources. The findings of this research demonstrate the superiority and uniqueness of iron compared to all available elements/materials. These findings may also give us a better understanding of mentioning “Iron” in the Holy Book of the Qur'an.